Interfacility Transfer Guidelines for Isolated Facial Trauma: A Multidisciplinary Expert Consensus. Issue 4 (29th July 2022) - Pontell, Matthew E.; Steinberg, Jordan P.; Mackay, Donald R.; Rodriguez, Eduardo D.; Strong, E. Bradley; Olsson, Alexis B.; Kriet, J. David; Kelly, Kevin J.; Ochs, Mark W.; Taub, Peter J.; Desai, Shaun C.; MacLeod, Stephen; et al.
Abstract : Background: The objective of this study was to develop guidelines for the transfer of patients with isolated craniomaxillofacial trauma. Methods: A national, multidisciplinary expert panel was assembled from leadership in national organizations and contributors to published literature on facial reconstruction. The final panel consisted of five plastic surgeons, four otolaryngologist–head and neck surgeons, and four oral and maxillofacial surgeons. The expert panelists' opinions on transfer guidelines were collected using the modified Delphi process. Consensus was predefined as 90 percent or greater agreement per statement. Results: After four Delphi consensus building rounds, 13 transfer guidelines were established, including statements on fractures of the frontal sinus, orbit, midface, and mandible, as well as soft-tissue injuries. Twelve guidelines reached consensus. Conclusions: The decision to transfer a patient with craniomaxillofacial trauma to another facility is complex and multifactorial. While a percentage of overtriage is acceptable to promote safe disposition of trauma patients, unnecessarily high rates of secondary overtriage divert emergency medical services, increase costs, delay care, overload tertiary trauma centers, and result in tertiary hospital staff providing primary emergency coverage for referring hospitals. These craniomaxillofacial transfer guidelines were designed to serve as a tool to improve and streamline the care of facial trauma patients. Such efforts may decrease the additional health care expenditures associated with secondary overtriage while decompressing emergency medical systems and tertiary emergency departments.